A scholarly inquiry into disciplinary practices in educational institutions - de Wet, Corene (NWU Education and Human Rights in Diversity Series, 2019)
This book is a collection of chapters based on original research dealing with issues of discipline and disciplinary practices in educational institutions. The aim of the book is to provide a scholarly and scientific perspective on the current state of discipline and disciplinary practices in schools and tertiary education settings. The issue of discipline is investigated from diverse paradigmatic and methodological perspectives, presenting empirical as well as also philosophical research. The empirical perspective includes quantitative (positivistic), qualitative (interpretive) and mixed methods (pragmatic), designs and worldviews. This book offers a ground-breaking contribution to the field of learner and student discipline, with insights into disciplinary practices and issues in educational institutions not hitherto researched, such as Technical Vocational Education and Training colleges and universities.